2020
DOI: 10.1016/j.drugalcdep.2020.107968
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy-based methadone dispensing and drive time to methadone treatment in five states within the United States: A cross-sectional study

Abstract: Background: Within the United States, there is a shortage of opioid treatment programs (OTPs), facilities which dispense methadone for opioid use disorder. It is unknown how pharmacy-based methadone dispensing, as available internationally, could affect methadone access. We aimed to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 42 publications
4
66
1
Order By: Relevance
“…Other research has shown that methadone treatment access is already limited, especially for rural populations ( Rosenblum et al, 2011 ). For example, research in other countries has shown that methadone dispensing through pharmacies can be safe, effective ( Calcaterra et al, 2019 ), and increase access ( Joudrey et al, 2020 ; Kleinman, 2020 ), especially during a public health emergency when OTPs may not be adequately prepared to make alterations in care delivery. Experts in the field suggest that while the easements in policies to increase the number of take-homes is recommended in the case of emergencies, the use of alternative forms of treatment delivery are also needed ( Cochran et al, 2020 ; Green et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other research has shown that methadone treatment access is already limited, especially for rural populations ( Rosenblum et al, 2011 ). For example, research in other countries has shown that methadone dispensing through pharmacies can be safe, effective ( Calcaterra et al, 2019 ), and increase access ( Joudrey et al, 2020 ; Kleinman, 2020 ), especially during a public health emergency when OTPs may not be adequately prepared to make alterations in care delivery. Experts in the field suggest that while the easements in policies to increase the number of take-homes is recommended in the case of emergencies, the use of alternative forms of treatment delivery are also needed ( Cochran et al, 2020 ; Green et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the long term, policies should change in favor of making methadone available in pharmacies, as is the case in Canada. A study showed that pharmacy-led methadone dispensing would significantly reduce the rural-urban disparity in access to MOUD, as rural census tracts have disproportionately long drive times to OTPs, many of which are located in urban settings ( Joudrey et al, 2020 ). Furthermore, this would contribute to addressing the stigma associated with receiving MOUD, especially through OTPs.…”
Section: Proposed Solutionsmentioning
confidence: 99%
“…This study obtained data on the location of and contact information for OTPs in the United States from the Behavioral Health Treatment Service Locator of the Substance Abuse and Mental Health Services Administration (SAMHSA) ( Substance Abuse and Mental Health Services Administration, 2020d ). The SAMHSA compiled the list based on responses to the National Substance Abuse Treatment Services Survey (N-SSATS) and have formed the basis of previous studies of the availability of health services by OTPs ( Gangopadhyaya et al, 2020 ; Joudrey et al, 2020 ). We restricted our study to the 1534 OTPs in the contiguous United States (including the District of Columbia) that the locator included as of April 10, 2020.…”
Section: Methodsmentioning
confidence: 99%